Numerical analysis of honeycomb-shaped polymeric foams using the FEM and the RPIM. (1st August 2021) - Nascimento, N.A.; Belinha, J.; Natal Jorge, R.M.; Rodrigues, D.E.S.
Abstract: The importance of cellular materials continues to increase in lightweight structural applications as more industries realize these materials are becoming more reliable, repeatable and allowing for lower production costs. Among all the common structural applications of cellular architected materials, cores for sandwich panels may perhaps be the most important one, and therefore, were the focus of this work. On the other hand, the fast-paced growth of computational power, in combination with the development of software and numerical methods such as Meshless Methods provide the necessary conditions to study intricate topologies which may offer improved mechanical properties for each different application. In this work, two periodic cellular topologies which are typically used in the cores of sandwich structures were designed, namely conventional honeycombs and re-entrant honeycombs, for 7 different values of relative density, and tested in two different in-plane directions in the linear-elastic domain. The Radial Point Interpolation Method (RPIM) is used in this study, for the first time in the literature, to simulate the elasto-static behaviour of honeycomb structures and provides advantages over the Finite Element Method (FEM) in this field.